2010
DOI: 10.1037/a0018814
|View full text |Cite
|
Sign up to set email alerts
|

Cultural mistrust and mental health help-seeking attitudes among Filipino Americans.

Abstract: As low as the rate of mental health help-seeking is among Asian Americans, Filipino Americans seek mental health services at a much lower rate even compared with other Asian Americans. Despite the field's progress in identifying and understanding factors that may influence mental health help-seeking attitudes among Asian Americans, despite research on other minority groups suggesting that cultural mistrust may influence attitudes toward seeking professional psychological help, and despite the abundance of lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
152
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 46 publications
10
152
1
2
Order By: Relevance
“…The discrepancy could be a product of the ethnic heterogeneity of the participants in the study. Among Filipino Americans, research suggests that loss of face was negatively associated with past utilization and propensity to seek help from mental health professionals, positively associated with willingness to seek help from lay networks, and not related to help seeking from general practitioners and folk healers (David, 2010;Gong et al, 2003). However, among Filipinos, loss of face was positively associated with intent to seek face-to-face and online counseling (Bello et al, 2013).…”
Section: Public and Private Stigma Hiya And Loss Of Facementioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancy could be a product of the ethnic heterogeneity of the participants in the study. Among Filipino Americans, research suggests that loss of face was negatively associated with past utilization and propensity to seek help from mental health professionals, positively associated with willingness to seek help from lay networks, and not related to help seeking from general practitioners and folk healers (David, 2010;Gong et al, 2003). However, among Filipinos, loss of face was positively associated with intent to seek face-to-face and online counseling (Bello et al, 2013).…”
Section: Public and Private Stigma Hiya And Loss Of Facementioning
confidence: 99%
“…Studies suggest that loss of face was negatively associated with indifference to stigma and psychological openness among Filipino Americans (David, 2010;Gong et al, 2003). Among Filipinos, loss of face was negatively associated with attitude towards counseling, and positively associated with perceived stigma for seeking help and receiving psychological help (Bello et al, 2013).…”
Section: Public and Private Stigma Hiya And Loss Of Facementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies found that cultural mistrust resulted in a preference by Black clients for Black counselors, negative attitudes toward seeking psychological treatment, and a propensity to terminate therapy prematurely (Sue & Sue, 1972;Townes, Chavez-Korell, & Cunningham, 2009). These findings have been generalized to other minority groups including Southeast Asians and Latinos (David, 2010;Shea & Yeh, 2008).…”
Section: Cultural Mistrust Of Mental Health Counselorsmentioning
confidence: 99%
“…Initially developed as a concept to describe the distrust Black Americans had towards White Americans, cultural mistrust encompasses an overall mistrust of White-dominated institutions such as the legal system, educational system, job settings, and government agencies (David, 2010). Many studies found that cultural mistrust resulted in a preference by Black clients for Black counselors, negative attitudes toward seeking psychological treatment, and a propensity to terminate therapy prematurely (Sue & Sue, 1972;Townes, Chavez-Korell, & Cunningham, 2009).…”
Section: Cultural Mistrust Of Mental Health Counselorsmentioning
confidence: 99%